Smart Healthcare Monitoring System Using IoT - Arunpradeep.N, Dr. G. Niranjana, Dr. G. Suseela (International Journal of Advanced Science and Technology, 2020)
In the health care sector, IoT plays a significant function. The people in the hospital who are seeking medical care are non-ambulatory, so if there is a method for forecasting illness it will be helpful for them. In Healthcare system latest trends of IOT is used. IOT software helps patients to reduce health-related threats and hospital expenses by gathering patient information and processing data using cloud services to exchange data sources. This system offers a cloud-based solution to a diagnostic framework for automatic cardiac disease that utilizes sensors to monitor specific patient parameters such as blood pressure, heart beat rate, respiration and temperature, etc. Here, hither project to predict cardiac attack by collecting sensor data and submitting the data to the doctor via cloud. Using this plan will save both specialist and patient time and easily make recommendations about follow up medical care and to receive it at any time and anywhere they need it. Through gathering data, the patient may receive appropriate and secure medical attention through tracking the current state of the patient collected by the cloud using IOT and displayed in LCD. Keywords: Medical sensors, Various Parameters, Cloud, Microcontroller, LCD, Healthcare Monitoring System and IoT.